Constructing authentic decisions: proxy decision making for research involving adults who lack capacity to consent - Shepherd, Victoria (Journal of medical ethics, 2021)
Research involving adults who lack capacity to consent relies on proxy (or surrogate) decision making. Proxy decisions about participation are ethically complex, with a disparity between normative accounts and empirical evidence. Concerns about the accuracy of proxies’ decisions arise, in part, from the lack of an ethical framework which takes account of the complex and morally pluralistic world in which proxy decisions are situated. This qualitative study explored the experiences of family members who have acted as a research proxy in order to develop an understanding of the ethical concepts involved, and the interactions between those concepts. Proxies described a complex process of respecting the wishes and preferences of the person they represented, whist integrating preferences with what they viewed as being in the interests of the person. They aimed to make a decision that was ‘best’ for the person and protected them from harm; they also aimed to make the ‘right’ decision, viewed as being authentic to the person’s values and life. Decisions were underpinned by the relationship between the person and their proxy, in which both trust and trustworthiness were key. Proxies’ decisions, based both on respect for the person and the need to protect their interests, arose out of their dual role as both proxy and carer. The findings raise questions about accounts which rely on existing normative assumptions with a focus on accuracy and discrepancy, and which fail to take account of the requirement for proxies to make authentic decisions that arise out of their caring obligations.